Timing, diagnosis, and treatment of surgical site infections after colonic surgery: prospective surveillance of 1263 patients. Issue 4 (December 2018) - Martin, D.; Hübner, M.; Moulin, E.; Pache, B.; Clerc, D.; Hahnloser, D.; Demartines, N.; Grass, F.
Summary: Background: Surgical site infections (SSIs) are the most frequent complication after colorectal surgery and have a major impact on length of stay and costs. Aim: To analyse the incidence, timing, and treatment of SSIs within 30 days after colonic surgery. Methods: This was a quality improvement project through retrospective analysis of consecutive colonic surgeries between February 2012 and October 2017 at Lausanne University Hospital (CHUV). SSIs were prospectively assessed by an independent national surveillance programme (www.swissnoso.ch ) up to 30 postoperative days. Treatment strategies including drainage of infection (direct wound opening or percutaneous) and surgical management were reviewed. Findings: The study cohort included 1263 patients with 532 procedures (42%) performed as emergencies. SSIs were observed in 271 patients (21%), occurring at median postoperative day (POD) 9 (interquartile range (IQR): 4–16). Specifically, 53 (4%) were superficial incisional, 65 (5%) deep incisional, and 153 (12%) organ space infections (anastomotic insufficiency included). Superficial incisional SSI occurred at a median of POD 10.5 (IQR: 7–15), deep incisional at a median of POD 10 (8–15) and organ space at a median of POD 8 (5–11). Diagnosis was performed post discharge in 64 cases (24%). Whereas 47% of organ space infections were detected by POD 7, this rate was only 26% for superficial and deep incisional infections (P = 0.003). Surgical management was necessary in 133 cases (49%), and the remaining cases were managed by drainage without general anaesthesia (138 cases, 51%). Conclusion: Organ space infections occurred early in the postoperative course, whereas incisional infections were mostly detected post discharge over the entire 30-day observation period, emphasizing the importance of proper follow-up using a systematic, complete and independent surveillance programme.